PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS IV MATERI LUAS PERSEGI DAN PERSEGI PANJANG - Fariza Putri Nabila; Conny Dian Sumadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low mathematical problem-solving abilities of fourth-grade students at SDIT Asshomadiyah, particularly in mathematics learning. Students experienced difficulties in understanding word problems, determining appropriate solution steps, and applying mathematical concepts in real-life situations. This study aimed to determine the effect of the Problem Based Learning (PBL) model on the problem-solving abilities of fourth-grade students on the topic of the area of squares and rectangles. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population of this study consisted of all fourth-grade students at SDIT Asshomadiyah, totaling 44 students. The sampling technique used was saturated sampling, with class IV-A serving as the experimental class and class IV-B as the control class. Data collection techniques included tests, observations, and documentation. The research instruments consisted of essay-based pretests and posttests to measure problem-solving abilities. The data were analyzed using normality tests and the independent sample t-test. The results showed that the implementation of the Problem Based Learning (PBL) model had an effect on students’ problem-solving abilities. This was indicated by the improvement in problem-solving ability scores in the experimental class, which was better than that of the control class. Therefore, the Problem Based Learning (PBL) model can be used as an alternative learning model to improve students’ mathematical problem-solving abilities on the topic of the area of squares and rectangles. Keywords: Mathematics, Problem Based Learning, Problem-Solving Ability